Strategy-Based Learning Planning To Improve The Quality Of Al-Qur'an Memorization: A Study At Two Tahfiz Islamic Boarding Schools - M. Munif (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
The quality of Qur’anic memorization in tahfiz institutions is not solely dependent on the cognitive capacity of students but also on the effectiveness of strategically designed instructional planning. Empirical realities indicate that many tahfiz institutions still lack structured, adaptive, and contextual learning strategies. This study aims to identify and analyze the key strategies employed in the planning of Qur’anic instruction to enhance the quality of memorization. A qualitative research approach with a multisite design was applied, involving two prominent Islamic boarding schools: Madrasatul Qur’an  (MQ) in Tebuireng Jombang and PPTQ Al-Ma’ruf in Juranguluh Kediri, Indonesia. Data were collected through in-depth interviews, participant observation, and document analysis, and were interpreted using the analytical framework of Miles, Huberman, and Saldaña. The findings revealed seven primary strategies implemented in a consistent and integrative manner: the bin nadzar program, tahfiz program, mudarasah, fasahah, tashih, tasmi’, and qira’at sab’ah. These strategies significantly contribute to enhancing memorization accuracy, articulation precision, and student discipline. The implications of this research emphasize the need for strategy-based instructional planning in tahfiz education that prioritizes not only memorization quantity but also quality and depth of internalization. This study opens pathways for developing contextual, measurable, and tradition-rooted models of Qur’anic learning within pesantren-based education systems.